Beitrag zur Chrysomelidenfauna Bulgariens (Coleoptera: Chrysomelidae). - Mohr, Karl-Heinz (Contributions to Entomology = Beiträge zur Entomologie, 1969)
The present paper deals with the Chrysomelidae species of Bulgaria, collected by different entomologists. The determination established 91 species, 12 of which were hiterto unknown in Bulgaria. Two of the species, Cryptocephalus prusians Suffrian and Luperus lydius Weise, were found for the first time in Europe. On new subspecies (Chrysomela vernalis muchei ssp. geogr. nov.) is described. Nomenclatural Acts muchei Mohr, 1969 (Chrysomela vernalis), sspec. n.